Edukasi Pemuda Harapan Bangsa Sehat dan Berprestasi Tanpa Rokok di Desa grojogan Kabupaten Nganjuk - Pramono, Deni; Al Birri, Gama Rizal; Saptorini (Kadiri University, 2023)
As the nation's hope, the youth play a crucial role in developing a country. They represent the next generation expected to bring progress and prosperity to the nation. However, the potential of the youth cannot be fully realized if the dangerous habit of smoking compromises their health. Smoking can have severe implications for the health of the youth, including risks of heart disease, respiratory issues, and cancer. Moreover, it can hinder academic and overall achievements in various fields. Therefore, educating the youth about the dangers of smoking, encouraging them to steer clear of this habit, and providing access to a healthy lifestyle are vital steps in the context of building a healthy and high-achieving nation. A community engagement program was conducted in Grojogan Village, Nganjuk District, East Java Province, to educate the youth about the hazards of smoking and motivate them to lead a smoke-free, healthy life. The method employed was an educative and participatory approach, utilizing a peer education model that involved groups of youths who had successfully quit smoking in providing guidance and information to their peers. The target participants were youths aged 15 to 25 from various youth communities. The respondent selection was carried out through an initial survey to identify youths who were currently smokers or at high risk of becoming smokers. The outcomes of this program include an increase in the knowledge of the youth regarding the dangers of smoking, a boost in motivation to quit smoking, and heightened awareness of the benefits of a smoke-free life. Furthermore, the program effectively mobilized groups of youths who had quit smoking to offer support and guidance to their peers. Consequently, this program has the potential to reduce the prevalence of smoking among the youth, positively impacting their health and achievements. Pemuda harapan bangsa memiliki peran krusial dalam pembangunan sebuah negara. Mereka adalah penerus generasi yang diharapkan membawa kemajuan dan kesejahteraan bagi bangsa. Namun, potensi pemuda tidak akan terwujud dengan baik jika kesehatan mereka terganggu oleh kebiasaan merokok yang berbahaya. Merokok dapat berdampak serius pada kesehatan pemuda, termasuk risiko terhadap penyakit jantung, penyakit pernapasan, dan kanker. Selain itu, rokok juga dapat menghambat prestasi akademik dan prestasi dalam berbagai bidang lainnya. Oleh karena itu, mendidik pemuda tentang bahaya merokok, mendorong mereka untuk menjauhi kebiasaan merokok, dan memberikan akses untuk hidup sehat merupakan langkah yang sangat penting dalam konteks pembangunan bangsa yang sehat dan berprestasi. Program pengabdian kepada masyarakat ini dilaksanakan di Desa Grojogan, Kabupaten Nganjuk, Provinsi Jawa Timur, dengan tujuan memberikan edukasi kepada pemuda mengenai bahaya merokok dan mendorong mereka untuk hidup sehat tanpa rokok. Metode yang digunakan adalah pendekatan edukatif dan partisipatif, dengan model pendidikan sebaya yang melibatkan kelompok pemuda yang telah berhasil berhenti merokok dalam penyuluhan kepada teman sebaya. Sasaran kegiatan adalah pemuda usia 15 hingga 25 tahun dari berbagai komunitas pemuda. Seleksi responden dilakukan melalui survei awal untuk mengidentifikasi pemuda yang merokok atau berisiko tinggi menjadi perokok. Hasil dari program ini mencakup peningkatan pengetahuan pemuda tentang bahaya merokok, peningkatan motivasi untuk berhenti merokok, dan peningkatan kesadaran akan manfaat hidup tanpa rokok. Program ini juga berhasil memobilisasi kelompok pemuda yang telah berhenti merokok untuk memberikan dukungan kepada rekan-rekan sebaya. Dengan demikian, program ini berpotensi mengurangi prevalensi merokok di kalangan pemuda, yang akan berdampak positif pada kesehatan dan prestasi mereka.